Stearidonic acid improves eicosapentaenoic acid status: studies in humans and cultured hepatocytes - Seidel, Ulrike; Eberhardt, Katharina; Wiebel, Michelle; Luersen, Kai; Ipharraguerre, Ignacio R.; Haegele, Franziska A.; Winterhalter, Peter; Bosy-Westphal, Anja; Schebb, Nils Helge; Rimbach, Gerald (Frontiers in Nutrition, 2024)
Background Ahiflower oil from the seeds of Buglossoides arvensis is rich in α-linolenic acid (ALA) and stearidonic acid (SDA). ALA and SDA are potential precursor fatty acids for the endogenous synthesis of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which are n3-long chain polyunsaturated fatty acids (n3-LC-PUFAS), in humans. Since taurine, an amino sulfonic acid, is often associated with tissues rich in n3-LC-PUFAS (e.g., in fatty fish, human retina), taurine may play a role in EPA- and DHA-metabolism. Objective To examine the capacity of the plant-derived precursor fatty acids (ALA and SDA) and of the potential fatty acid metabolism modulator taurine to increase n3-LC-PUFAS and their respective oxylipins in human plasma and cultivated hepatocytes (HepG2 cells). Methods In a monocentric, randomized crossover study 29 healthy male volunteers received three sequential interventions, namely ahiflower oil (9 g/day), taurine (1.5 g/day) and ahiflower oil (9 g/day) + taurine (1.5 g/day) for 20 days. In addition, cultivated HepG2 cells were treated with isolated fatty acids ALA, SDA, EPA, DHA as well as taurine alone or together with SDA. Results Oral ahiflower oil intake significantly improved plasma EPA levels (0.2 vs. 0.6% of total fatty acid methyl esters (FAMES)) in humans, whereas DHA levels were unaffected by treatments. EPA-levels in SDA-treated HepG2 cells were 65% higher (5.1 vs. 3.0% of total FAMES) than those in ALA-treated cells. Taurine did not affect fatty acid profiles in human plasma in vivo or in HepG2 cells in vitro. SDA-rich ahiflower oil and isolated SDA led to an increase in EPA-derived oxylipins in humans and in HepG2 cells, respectively. Conclusion The consumption of ahiflower oil improves the circulating levels of EPA and EPA-derived oxylipins in humans. In cultivated hepatocytes, EPA and EPA-derived oxylipins are more effectively increased by SDA than ALA.